AB0016 Chromatin localization of survivin in cd4+ t-cells of patients with rheumatoid arthritis - Andres, S.; Andersson, K.M.; Damdimopoulos, A.; Katona, G.; Bokarewa, M.I. (Annals of the rheumatic diseases, 2018)
BackgroundOncoprotein survivin emerged as an important player in the pathogenesis of rheumatoid arthritis (RA). Results of genome-wide study suggest that survivin may take part in transcription stimulation of the RA-specific genes.ObjectivesTo identify and describe survivin-dependent differences in transcription pattern between CD4+ T-cells of RA patients and healthy subjects focusing in particular on a subset of genes involved in maturation of Th1 and Th17 cells.MethodsCD4+ T-cells were isolated from PBMC of 3 RA patients and 5 non-smoking and 2 smoking healthy controls using a positive selection and activated by Pam3cys+Concanavalin A+LPS. Chromatin immunoprecipitation (ChIP) was done using rabbit polyclonal anti-Survivin, purified DNA was prepared into libraries using ThruPLEX (Rubicon) and sequenced using Hiseq 2000 (Illumina). Resulting fastq sequencing files were mapped to the human reference genome (hg38) using the STAR aligner. Peaks were associated with the closest transcription start site. Enriched peak regions (p<10–5) were identified in survivin-ChIP samples above background (“input”) using the Homer software. The peaks were analysed using gene ontology (GO) technique as implemented in GOrilla and GSEA software. The genes, scored high in RA and not present/low in any controls or vice versa were identified. The enriched GO groups were searched for presence of Th1/Th17 regulating genes.ResultsWe identified 11 145 survivin-bound chromatin sequencies. Out of them, GO technique indicated 770 genes in RA samples (7.3%) and 766 genes in healthy controls (19.5%) which were annotated and enriched (>log-5) in GO terms. In the screening for genes regulating maturation of Th1/Th17 cells, CBLB, IRF1, STAT3, SGK1 and TNFSF14 were identified among the genes enriched in RA samples, while EGR3 and ETS1 were enriched only in healthy controls. Additionally, transcription factors Ezh2, Rad21, Ctbp2 and Suz12 were identified as common for both RA and healthy groups genes, associated with significant GO enrichment.ConclusionsThis study confirms the role of survivin as a transcription mediator in CD4 +T cells and is suggested to influence multiple genes involved in RA pathology.References[1] Andersson KME, et al. Pathogenic Trans differentiation of Th17 Cells Contribute to Perpetuation of Rheumatoid Arthritis during Anti-TNF Treatment. Mol. Med. 2015;21:536–43.[2] Hu D, et al. Transcriptional signature of human pro-inflammatory TH17 cells identifies reduced IL10 gene expression in multiple sclerosis. Nat. Commun. 2017;8:1600.Disclosure of InterestNone declared